Political economy of immigration in Germany: attitudes and citizenship aspirations - Martin Kahanec; Mehmet Serkan Tosun (Institute for the Study of Labor (IZA), 2007)
This paper examines resident foreigners' interest in German citizenship. The study focuses on the roles played by attitudes towards foreigners, political interest of foreigners, intergenerational conflict between natives and foreigners and among foreigners themselves, and regional differences in public finances. To address our research questions, we use a unique dataset from a survey of foreign residents in the German States provided by the Central Archive for Empirical Social Science Research of the University of Cologne. We find that some of the significant negative factors that affect citizenship interest are negative attitudes towards foreigners and generational conflict within foreigner families. On the other hand, interest in political participation, German schooling, home ownership, being born in Germany and being a citizen of non-EU country are important positive factors. Negative experience of foreigners in terms of hostile attitudes, lack of voting rights, or uncertainty of the possibility to stay in Germany mainly discourage foreign residents who actively participate in the labor market, have more years of schooling, and are younger.
Keywords: 330; Immigration; attitudes; citizenship; voting; Migranten; Staatsangehörigkeit; Ausländer; Meinung; Deutschland